Surface morphologies of gold nanoparticles electrodeposited on glassy carbon electrode and applicability in detection of Hg(II) at trace concentration - Phong, Pham Hong; Anh, Nguyen Hoang; Hung, Le Quoc; Thu Ha, Vu Thi (Vietnam Journal of Chemistry, 2014)
In the present study, we showed the variation of surface morphologies of gold nanoparticles (Au-NPs) on glassy carbon electrode (GCE) obtained by electrochemical method via controlling the electrochemical deposition time and stirring condition. The size in diameter of gold particles was not significantly changed with the variation of these conditions, whereas their surface coverage was strongly dependent. This behavior governed the enhancement of the peak current on the differential pulse voltammograms for reduction of Hg(II) bound to 4-pyridineethanethiolate self-assembled on gold particles through chemical preconcentration. This result clearly proves the applicability of the modified electrode in detection of Hg(II) at trace concentration. Keywords: Self-assembled monolayers, gold nanoparticles, 4-pyridineethanethiol.